Pangium edule, an Almost Forgotten Plant and Its Potential - T Partomihardjo; Rugayah . (Media Konservasi, 1989)
Pangi (Pangium edule Reinw.) is one of the Indonesian plant, which is recently becoming rare, especially in Java and Sumatera. Based on the herbarium collections, the plant is distributed throughout Indonesia. It grows well below 300 m above sea level, but it is found up to 1000 m a.s.l., in primary and secondary rain forests, also a long river banks, in teak forests, on dryland, stony or clay soils. Pangi is known as a poisonous tree, but the seeds have been extensively utilized for many favorite dishes. The fresh leaves or seeds or the oil are used as an anticeptic, disinfectant or antiparasitic, to preserve meat and to kill fish, etc. The seeds seem to be dispersed by water, because they have excellent floating capacity. However, in Bacan Island, North Maluku, they might also be dispersed by black monkeys.